Engaged Pentecostalism in Asia: Civic Welfare, Public Morality, and Political Participation - Cornelio, Jayeel S (Archīum Ateneo, 2021)
This chapter presents the scholarly landscape of the social and political engagements of Pentecostal churches in Asia. Drawing on the extensive literature on Pentecostalism in its various regions; the aim of this essay is to characterize these engagements. Three forms of social and political engagements are salient. The first is civic welfare; referring to the delivery of development and humanitarian assistance by Pentecostal churches to address the needs of local communities. These needs include educational assistance; healthcare; and basic nutrition. The second concerns public morality. In different countries; Pentecostal churches have resisted policies that they consider inimical to social progress for violating divine principles. These issues tend to revolve around same-sex marriage and gender equality. In this way; Pentecostals are defending what they consider to be God’s mandate for the nations by resisting what they believe are godless policies. The third form is direct engagement in politics. Scholars have documented the growing presence of Pentecostal churches in electoral politics. In some cases they have even formed political parties to endorse or field their own candidates.After explaining these salient characteristics; the essay then turns to conceptualizing the social and political work of Pentecostalism in Asia. Nuancing earlier writings about the rise of progressive Pentecostalism in the Global South; a more appropriate way of referring to the Asian experience is “engaged Pentecostalism”. The concept refers to the movement within Pentecostal and Charismatic groups; driven by a desire to be relevant and to correct what they consider social and political evils; to be involved in the affairs of the present. It recognizes the diverse expressions of Pentecostal involvements in society and the religious and political worldviews that underpin them. In effect; “engaged Pentecostalism” not only contests the misconceptions about Pentecostals being preoccupied with conversion or the eschatology. It also recognizes the implications of Pentecostal work on politics and society; inspired by an array of convictions including social justice; moral conservatism; and religious nationalism.